Standardisasi Laboratorium IPA SMPN 3 Sumenep - Nisfil Maghfiroh Meita (University of Bengkulu, 2018)
AbstraCT[Standardization of science laboratory at SMPN 3 Sumenep]. Schools must have laboratory infrastructure in addition to other educational equipment and tools. Therefore, students can construct thinking from the concrete towards abstract thinking. To get a good laboratory, a standardized laboratory is needed in accordance with national education standards in Indonesia, especially standard facilities and infrastructure. The objectives of this research were to describe 1) the science laboratory equipment of SMPN 3 Sumenep; 2) science laboratory management of SMPN 3 Sumenep; and 3) suitability of the standardization of the science laboratory of SMPN 3 Sumenep with Indonesian government regulation of PERMEN No. 24, 2007. The subject of the research is SMPN 3 Sumenep. This research is a qualitative descriptive study. Data collection techniques use interviews, observation, and document scrutiny. The instrument used was an observation instrument with a Guttman scale. Data validity test is done by triangulating data sources. Data were analyzed using models from Miles and Huberman with the stages of data collection, data reduction, data presentation, and conclusion drawing. The results showed that 1) Science laboratory equipment at Sumenep Junior High School 3 had a percentage of 86.34% with good / ideal criteria and in accordance with the standardization of PERMEN No. 24 of 2007; 2) Management of science labs at Sumenep Junior High School 3; and 3) Science Laboratory of SMPN 3 Sumenep is a good / ideal laboratory for SMP Science Laboratory and has fulfilled standardization based on PERMEN No. 24 of 2007. Keywords: Standardization; Science Laboratory; Indonesian government regulation.